2019
DOI: 10.4049/jimmunol.1900229
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D Status Is Associated with Epithelial–Mesenchymal Transition in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Vitamin D deficiency is correlated with the increased morbidity of chronic obstructive pulmonary disease (COPD). However, the mechanisms underlying these effects have largely remained elusive. This study analyzed the correlations among COPD, vitamin D concentration, and epithelial-mesenchymal transition (EMT). Ninety-five patients with newly diagnosed COPD and 190 age-and sex-matched healthy subjects were recruited for this research. Serum 25(OH)D levels were detected, and pulmonary EMT biomarkers and TGF-b/Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 47 publications
0
28
0
1
Order By: Relevance
“…One study even reported a decrease in CYP24A1 mRNA level in tissue from COPD patients compared to control tissue. As these subjects had significantly lower serum 25(OH)D levels [26] compared to the serum 25(OH)D levels in our group, it might explain why CYP24A1 expression levels were comparable between both our groups.…”
Section: Discussionmentioning
confidence: 43%
“…One study even reported a decrease in CYP24A1 mRNA level in tissue from COPD patients compared to control tissue. As these subjects had significantly lower serum 25(OH)D levels [26] compared to the serum 25(OH)D levels in our group, it might explain why CYP24A1 expression levels were comparable between both our groups.…”
Section: Discussionmentioning
confidence: 43%
“…For total protein extraction, 60 mg placental sample was prepared using 600 µL of RIPA buffer containing 1% PMSF. The details of the method used were based on a previous study 22 . For Western blotting, placental protein was separated electrophoretically by SDS‐PAGE and passed on to a PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D, a secosteroid hormone, is famous for its classical functions in calcium uptake and bone metabolism (4,8). Currently, vitamin D is discovered in some nonclassical actions, such as immunomodulation, antioxidant effect, antiapoptosis effect, regulating epithelial-mesenchymal transition, and anti-inflammatory activity (9)(10)(11)(12)(13)(14). Recently, numerous researchers indicated that 1,25(OH) 2 D 3 , the active form of vitamin D, recovered elastaneinduced reduction of forced expiratory volume in 1 s (FEV1) to the forced vital capacity (FVC) and alveolar destruction in a mouse model of COPD (15).…”
mentioning
confidence: 99%
“…Vitamin D has an anti-inflammatory role in the lung (13,19). Several reports showed that vitamin D could repress inflammation via reinforcing the interaction between VDR and NF-kB p65 subunit (20).…”
mentioning
confidence: 99%